Strategi Pemasaran 5.0: Analisis Pengaruh Prediksi, Konteks, dan Augmented Reality terhadap Kinerja Pemasaran - Olanda, Aditiya; Perdana, Aga Widyah; Huzein, Ilham; Gassama, Alhagie; Jabbi, Ebrima; Bachtiar, Arief (Economic Reviews Journal, 2025)
This study aims to analyze the influence of Predictive Marketing, Contextual Marketing, and Augmented Reality on Marketing Performance. The research employs a quantitative approach with path analysis using Partial Least Square (PLS). The findings reveal that all three independent variables positively and significantly affect marketing performance. Predictive Marketing contributes through historical data analysis to predict customer trends. Contextual Marketing supports the personalization of content relevant to customer needs in real-time, while Augmented Reality technology creates interactive and unique customer experiences. This study highlights the importance of integrating technology into marketing strategies to enhance company performance in the digital era.